Outcome of Medical versus Surgical Methods in Second Trimester Abortion - Lama, S; Chherty, S (Nepal Journal of Obstetrics and Gynaecology, 2016)
Aims: This study aimed to assess the effectiveness of medical versus the surgical methods and to determine the outcome of both the methods with respect to complications like incomplete abortion, bleeding and sepsis. Methods: This study was conducted at BP Koirala Institue of Health Sciences. Total of 80 patients, 40 in each group were enrolled in the study. For medical abortion group, Mifepristone 200mg orally followed by Misoprostol 400 mcg vaginally were given until the patient expelled the fetus. In surgical group, cervical priming was done with Misoprostol followed by dilatation and evacuation. The outcome of both medical and surgical abortions were compared in terms of amount of blood loss and associated complications like retained placenta and sepsis. Results: The overall complications were more in the medical group with 11.25% vs 2.5% in the surgical group (p value=0.02), with higher incidence of retained placenta (8 vs 0) and a higher amount of blood loss (129.20 +/- 20.4 ml vs 70.89 +/- 11.2 ml, p value <0.001) requiring blood transfusion. Conclusions: This study demonstrated that the surgical method is a more effective and safer procedure as compared to medical method. The complication rates were lower and it was also more cost effective.